Nerve Ultrasound Distinguishes Non-Inflammatory Axonal Polyneuropathy From Inflammatory Polyneuropathy With Secondary Axonal Damage - Brünger, Jil; Motte, Jeremias; Grüter, Thomas; Mork, Hannah; Bulut, Yesim; Carolus, Anne; Athanasopoulos, Diamantis; Yoon, Min-Suk; Gold, Ralf; Pitarokoili, Kalliopi; Fisse, Anna Lena (Frontiers in Neurology, 2022)
Introduction Chronic inflammatory demyelinating polyneuropathy (CIDP) may have a similar clinical and electrophysiological presentation to non-inflammatory axonal polyneuropathies (NIAP) when secondary axonal damage occurs. We aimed to investigate if nerve ultrasound can help to differentiate CIDP with additional secondary axonal damage from NIAP. Methods In a retrospective analysis, the cross-sectional area (CSA) of the peripheral nerves measured by ultrasound at six suitable nerve sites was compared in 95 patients with CIDP and 82 patients with NIAP. We developed the adjusted Bochum ultrasound score (aBUS) ranging from 0 to 6 resulting from number of sites with enlarged CSA (median, ulnar, radial, sural nerve). Results Mean CSA of CIDP patients was enlarged at all six nerve sites compared with mean CSA of NIAP patients. 21 CIDP patients did not meet 2010 electrophysiological diagnostic criteria (European Academy of Neurology/Peripheral Nerve Society Guideline, EFNS/PNS criteria) for CIDP at examination timepoint but only in further follow up, while 25 patients with NIAP fulfilled electrophysiological EFNS/PNS criteria for CIDP as ‘possible’ or ‘probable’ CIDP. To increase diagnostic power, we included aBUS measured by ultrasound in patients classified as ‘possible’ or ‘probable’ resulting in an improved specificity of 94% and a sensitivity of 59%, compared to a specificity of the EFNS/PNS criteria alone of 60% and sensitivity of 78%. Conclusion Using nerve ultrasound and the aBUS as a complementary method to distinguish CIDP from NIAP in case of secondary axonal damage can facilitate diagnosis of CIDP.